Factors protecting against progression of myopia in school students exposed to societal change in Vietnam: a 3-year cohort study - Kyoko Ohno-Matsui; Keiko Nakamura; Kaoruko Seino; Xuan Minh Tri Tran; Hoang Thuy Linh Nguyen; Thao Vi Tran; Tae Igarashi-Yokoi; Thang Van Vo (BMJ Open)
Objectives To elucidate the incidence of myopia, progression of refractive error, axial length (AL) elongation and factors associated with myopia in secondary school students in Vietnam.Design Prospective cohort study.Settings Hue Healthy Adolescent Cohort Study, Hue City, Vietnam.Participants 3-year longitudinal data were available for 355 secondary school students (mean age 11.60±0.36, 46.8% girls). Noncycloplegic refraction and AL measurements were performed at baseline and the 3-year follow-up examinations.Primary and secondary outcome measures The primary outcomes were myopia incidence and progression. Myopia, emmetropia and hyperopia were defined as spherical equivalent (SE)≤−1.0 diopters (D), −0.5 D<SE < +0.5 D and SE ≥ +0.5 D in the right eye, respectively. The cumulative incidence of myopia was defined as the proportion of students who were not myopic at baseline but who subsequently developed myopia during the follow-up period. Factors associated with myopia incidence and progression were analysed using logistic and linear regression models, respectively.Results Baseline mean SE and AL were −0.94±1.66 D and 23.36±0.93 mm, respectively. The cumulative and annual incidences of myopia were 40.6% and 12.5%, respectively. Spending more time outdoors was associated with a significantly decreased incidence of myopia (adjusted OR 0.499; 95% CI: 0.329–0.757), less myopic SE progression (β=0.337; 95% CI: 0.254, 0.640) and slower AL elongation (β=−0.289; 95% CI: −0.202 to –0.071). In contrast, a study using computers was significantly associated with greater myopic progression in SE (β=−0.184; 95% CI: −0.699 to –0.112) and AL elongation (β=0.208; 95% CI: 0.062, 0.263).Conclusion This longitudinal assessment revealed both myopia incidence and progression and identified myopia-risk and myopia-protective behavioural factors in a Vietnamese cohort of secondary school students. The results highlight the high prevalence and considerable incidence of myopia, and the need for further effective strategies to reduce the risk of myopia by managing computer time and increasing outdoor time.